Membaca, Gaya Hidup dan Kapitalisme: Kajian tentang Reading for Pleasure dari Perspektif Cultural Studies - RAHMA Sugihartati (Graha Ilmu, 2010)
Cultural studies on reading behaviour for pleasure among urban youth in Indonesia.